Optimalisasi Media Below the Line pada LRT Palembang dalam Upaya Perlindungan Kaum Perempuan - Eci Meiliana, Eci Meiliana; Isna Wijayani , Isna Wijayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Below the line media is promotional media that is active in nature, this media interacts directly with consumers because of its nature which makes it easier for consumers to immediately absorb the message conveyed. Transportation as a medium of communication is a form of change over time. This problem goes hand in hand with the emergence of new media, media with a smaller scope such as Below The Line Media which allows very specific target audience segmentation. Promotional media is divided into two types, namely Above The Line and Below The Line. Above the Line is promotional media which is carried out usually using television, radio, print media, billboards, etc. Below the line media is promotional media which is active in nature, this media interacts directly with consumers. The aim of this research is to find out how Below the Line media is implemented at the Palembang LRT (Light Rail Transit) Station. This research was conducted using qualitative with a descriptive approach, where qualitative research can be interpreted as research that uses data that is objective and appropriate to the existing problems. Bellow the Line media at the station for LRT users is actually effective for LRT service users, for example LRT service users see the existing promotional X-banners and are interested, but for people who have not used the LRT it is actually less effective. And for the protection of women on the LRT, I think it is safe and comfortable considering that at every station there are waiting seats specifically for mothers, pregnant women and the elderly, and in the carriages, there are also seats specifically for pregnant women, the elderly and disabled, and in The trains also have security on duty so that LRT service users feel safe. Below the line media is an important part in introducing a product or service to users and consumers. Optimizing below the line media in an effort to protect women on the Palembang LRT. The use of below the line media in the LRT station environment is optimal for Palembang LRT service users, however for a wider reach, other media are needed to help optimize Below The Line Media, and to ensure security in the LRT area, considering that at each station there are always officers ready to help, and security to maintain security around the LRT station area.